The Emergence of Alternative Financing Models: An In-depth Analysis of Revenue-Based Financing - Dey, Arnab (Journal of Global Economy, Business and Finance, 2024)
This study examines the emergence of revenue-based financing (RBF) as an alternative funding model for startups and growth-oriented companies. Through comprehensive literature analysis and market trend evaluation, the research investigates RBF's conceptual foundations, market dynamics, and strategic implications for both startups and investors. The findings reveal that RBF offers a unique balance between debt and equity financing, providing companies with capital without diluting ownership while tying repayments to revenue performance. The global RBF market is projected to reach $3.38 billion by 2023, driven by the changing structure of the economy and the growing demand for flexible financing options. The study concludes that RBF has the potential to transform the startup funding landscape, fostering a new generation of companies focused on sustainable growth. However, challenges such as standardization and regulation need to be addressed. This research contributes to the understanding of evolving financial instruments in the context of the innovation economy.